Development of chemistry laboratory guides based on chemoentrepreneurship (Cep) for odd semester in science class second grade - Sakdimah Sakdimah; Latisma Dj; Indang Dewata (International Conferences on Educational, Social Sciences and Technology)
Unemployment in Indonesia is dominated by high school graduates, this is due to limited job vacancy available, and generally high school graduates do not have the skills qualifications expected by the world of work. CEP is a chemical approach that links the material being studied with a real object. This research aims to develop a chemistry guide of chemistry high school chemoentrepreneurship (CEP) for the odd semester of class XI IPA. This research was conducted using 4D Models. The result of the development got the product validity level is 0.84 and the test of teacher practicity and student of SMA N 5 with value 0,83, teacher of MGMP with value 0,88. Based on the validation and practicality that has been implemented, Chemoentrepreneursip (CEP) Chemical Work Practice Guides (CEP) can be used as a learning resource and can improve life skill (skill) of the students.